Does your neighborhood invite you to walk? Analysis of pedestrian perception of walking conditions - Medeiros, Amanda Anselmo de; Vasconcelos, Ana Cecília Feitosa de; Barbosa, Amanda de Paula Aguiar (Revista de Administração da UFSM, 2024)
Purpose: The article aims to analyze walkability conditions in the Liberdade neighborhood, Campina Grande, Paraíba, from the perspective of pedestrians. In this context, the goal is to understand the conditions of movement, including sidewalk quality, mobility, public safety, road safety, and the environment, identifying areas for improvement for decision-making by the municipal government. Design/Methodology/Approach: The research is qualitative, using an analytical and comparative approach. Data collection involved bibliographic and documentary research and semi-structured interviews, conducted both in-person and online over eight days. The sample included 15 participants, predominantly with higher education, residing in Liberdade. Results: The study revealed inadequate walkability conditions in Liberdade, highlighting irregular sidewalks, a lack of accessibility, and precarious public safety. The research emphasized the need for investments to improve mobility and create a safe environment. The positive perspective of pedestrians regarding attractions such as parks was also emphasized. Limitations/Implications of the Research: Acknowledging limitations in the results, the research focused on Liberdade, indicating the need for further studies in other neighborhoods of Campina Grande. Practical implications include the need for investments in infrastructure and maintenance. Social Implications: The findings highlight the importance of public awareness regarding participation in urban planning to enhance pedestrian conditions in the city’s urban spaces. Originality/Value: Contributing to urban management and sustainability, the study provides insights into urban expansion and its consequences. It emphasizes the democratic and participatory role of pedestrians in reflections on urban walkability.